1987
DOI: 10.1128/mcb.7.9.3147
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Xenopus egg S6 kinase II recognize S6 kinase from progesterone- and insulin-stimulated Xenopus oocytes and from proliferating chicken embryo fibroblasts.

Abstract: Ribosomal protein S6 becomes highly phosphorylated during progesterone-or insulin-induced maturation of Xenopus laevis oocytes. We have previously purified an Mr 92,000 protein as one of the major S6 kinases from Xenopus unfertilized eggs. In this paper we confirm by renaturation of activity from a sodium dodecyl sulfate-polyacrylamide gel that this protein is an S6 kinase. This enzyme, termed S6 kinase II (S6 K II), was used for the preparation of polyclonal antiserum. Immunocomplexes formed with the antiseru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
49
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 53 publications
1
49
0
Order By: Relevance
“…Studies with this antiserum have revealed that progesterone-or insulin-stimulated oocytes contain an antigenically related enzyme. Furthermore, anti-S6KII antiserum reacts with an S6 kinase activity found in extracts of chicken embryo fibroblasts that had been stimulated with serum or transformed by Rous sarcoma virus (13). These results indicate that S6KII or an antigenically related S6 kinase(s) is subject to mitogenic stimulation in various cell types.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Studies with this antiserum have revealed that progesterone-or insulin-stimulated oocytes contain an antigenically related enzyme. Furthermore, anti-S6KII antiserum reacts with an S6 kinase activity found in extracts of chicken embryo fibroblasts that had been stimulated with serum or transformed by Rous sarcoma virus (13). These results indicate that S6KII or an antigenically related S6 kinase(s) is subject to mitogenic stimulation in various cell types.…”
mentioning
confidence: 64%
“…This event is mediated by a protein kinase activity that can be detected readily by phosphorylation of 40S subunits in vitro. The regulation of this enzyme activity is of interest because of the wide variety of agents that activate the kinase including serum, oncogene products, and phorbol ester in cultured cells (9)(10)(11) and insulin and progesterone in Xenopus oocytes (12,13). Although these agents initially act through different receptors, the pathways apparently converge to activate a single enzyme or a limited number of distinct enzymes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…RSK is activated in response to a broad range of cellular perturbations (16,32,33), including oncogenic transformation (32), insulin (17,32), growth factors (33), phorbol esters (16,33), growth hormone, changes in cAMP levels, heat shock, ionizing radiation, and T cell receptor activation (16,17,32,33). The p90 RSK signal transduction pathways are involved in cell growth, proliferation, differentiation, and apoptotic death (16) (29), but this antibody shows some cross-reactivity with RSK2 and RSK3 when phosphorylated at the homologous serine.…”
mentioning
confidence: 99%
“…Some S6Ks have been identified and characterized for example in progesterone-and insulin-treated Xenopus eggs termed S6K II (S6K II, p92) different from S6K I (Erikson et al 1987), differential role in Xenopus embryogenesis (S6K; p70) (Schwab et al 1999), in Rana oocytes (S6K; p83) (Byun et al 2002), in porcine oocytes (Sugiura et al 2002), and G1 phase after completion of meiosis II in starfish unfertilized eggs (Mori et al 2006) but not in mouse oocytes (Dumont et al 2005). S6K (p90 Rsk ) inhibits the degradation of cyclin B by anaphase-promoting complex/cyclosome (APC/C) and results the second meiotic metaphase arrest .…”
Section: S6 Kinase (S6k)/ Rsk Protein Kinase I/ii (Rsk)mentioning
confidence: 99%